Impact of sport on personality development - Jurayevich, Murodov Jaxongir (Middle European Scientific Bulletin, 2021)
In recent years, the sport is becoming more popular among people, but few know about its main features. So the main goal of this work is to show how this sphere of human activity may affect not only physical health, but also on the formation of moral personality